2020
DOI: 10.1101/2020.08.19.253369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A rapid and efficient screening system for neutralizing antibodies and its application for the discovery of potent neutralizing antibodies to SARS-CoV-2 S-RBD

Abstract: Neutralizing antibodies (Abs) have been considered as promising therapeutics for the prevention and treatment of pathogens. After the outbreak of COVID-19, potent neutralizing Abs to SARS-CoV-2 were promptly developed, and a few of those neutralizing Abs are being tested in clinical studies. However, there were few methodologies detailly reported on how to rapidly and efficiently generate neutralizing Abs of interest. Here, we present a strategically optimized method for precisive screening of neutralizing mon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 41 publications
4
21
0
Order By: Relevance
“…2b, Table 1). Two of them (58G6 and 510A5) showed consistent results with our previous findings 6 . The other 16 potential NAbs blocked authentic SARS-CoV-2 with the IC 50 ranging from 0.043 to 0.153 μg/mL, and they neutralized SARS-CoV-2 pseudovirus with similar IC50 (Extended Data Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…2b, Table 1). Two of them (58G6 and 510A5) showed consistent results with our previous findings 6 . The other 16 potential NAbs blocked authentic SARS-CoV-2 with the IC 50 ranging from 0.043 to 0.153 μg/mL, and they neutralized SARS-CoV-2 pseudovirus with similar IC50 (Extended Data Fig.…”
Section: Resultssupporting
confidence: 92%
“…In our previous study, at least 50% S-RBD specific mAbs derived from the memory B cells were found to be NAbs 6 . Here, we focused on the top 20 potential NAbs for their functional characterization and the neutralizing mechanism study, in detail.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations